KARAKTERISTIK PENDERITAHIPERTENSI DENGAN KOMPLIKASI RAWAT INAP DI RUMAH SAKIT UMUM DAERAH (RSUD) DR. HADRIANUS SINAGA PANGURURAN KABUPATEN SAMOSIR TAHUN 2015 - Betaria Sinaga; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Hypertension is a condition that the blood pressure were increased. This is  due to the work hard of heart to pump the blood to supply oxygen. In 2013, the highest was Bangka Belitung (30.9%), followed by South Kalimantan (30.8%), East Kalimantan (29.6%) and West Java (29.4%), while in North Sumatra (24.7%). The purpose of this study is to the identify the characteristics of Hypertension patients with complications who were hospitalized at dr. Hadrianus Sinaga Hospital, Samosir in 2015. This is descriptive study with case series design. The population and sample were 196 people. The data was secondary data and an analyzed by using Chi-Square, Kolmogorof-smirnov and Anova. The result showed that the highest proportion of hypertension patients with complications were in the age 50-54 years (35.7%), female (52.6% ), Bataknese (100%), Protestants (74%), elementary education (35.2%), farmers/ workers/fishermen (36.7%), sub Pangururan (61.7%), moderate hypertension (38.8%), weak (35.7%), Cardiovascular Disease (58,2%), average length of stay (3.86 days), BPJS (63.3%), PAPS (84.2%). There was no significant difference proportion of age, gender, hypertension degrees and average length of stay by the types of complications hypertension, and the types of complications hypertension by the state when return. In was suggested that hospital should increase health promotion regarding hypertension including rish factors and prevention to the community specifically to the patients. Hypertension patients should monitoring the blood pressure regulary and treatment and change a healthy lifestyle. Keywords: Characteristics of patients, Hypertension with complications